Cyclosporin, Tacrolimus, Mycophenolic Acid, and Dexamethasone Suppress Peripheral Blood Mononuclear Cell Proliferation and Inhibit Interferon-Gamma, IL-10 and IL-13 Production In Vitro - Abdel-Rahman Youssef (Turkish Journal of Immunology)
Objective: The primary goals of immunosuppressive therapy are to prevent graft rejection and to improve graft and patient survival. Long-term maintenance therapy after kidney transplantation includes cyclosporine A (CsA), tacrolimus (FK506), mycophenolic acid (MPA), and dexamethasone (Dex). This study aimed to determine the effects of these immunosuppressants on the proliferation of human peripheral blood mononuclear cells (PBMC) and the production of interferon-gamma (IFN-γ), interleukin (IL)-10, and IL-13 in vitro. Materials and Methods: Human PBMC were isolated and stimulated with an immobilized anti-CD3 (OKT3) monoclonal antibody in the absence (control) or presence of immunosuppressants. Additionally, unstimulated cells were cultured without anti-CD3 or immunosuppressants. On day 3 of cell culture, PBMC proliferation was assessed by 3H-thymidine incorporation, and cytokine production of IFN-γ, IL-10, and IL-13 was measured by ELISA. Results: CsA, FK506, MPA, and Dex inhibited PBMC proliferation and the production of IFN-γ, IL-10, and IL-13. CsA (100-1000 ng/ mL) and FK506 (1-10 ng/mL) inhibited PBMC proliferation significantly (p<0.05). All concentrations of MPA (0.01-10 μg/mL) and Dex (10-4-10-8 M) inhibited PBMC proliferation (p<0.05). High doses of CsA (100 ng/mL), MPA (1000 ng/mL), FK506 (10 ng/mL), and Dex (10-7 M) significantly inhibited IFN-γ, IL-10, and IL-13 significantly inhibited (p<0.05), while low-dose MPA (10 ng/mL) significantly increased IL-10 and IL-13 levels (p<0.05). Conclusion: The maintenance immunosuppressive regimen at therapeutically relevant concentrations including CsA (100 ng/mL), FK506 (10 ng/ mL), MPA (1 μg/mL), and Dex (10-6-10-7 M) suppressed PBMC proliferation and inhibited IFN-γ, IL-10, and IL-13 production in vitro.